Evaluation of two cucurbits (Genus: Momordica) for gastroprotective and ulcer healing activity in rats - Fernandopulle, B.M.R.; Ratnasooriya, W.D.; Karunanayake, E.H. (My University, 1996)
The gastioprotective acii\il.y of the tVuit extracts of two cucurbits Momordica cliaraniia and dioica -A as evaluated by inducing experimental gastric ulcers in the rat. Both frL'ii extracts (1 inL/lOOg) significantly inhibited the dcvelopmfnt of absolute ethano! and aspirin induced acute ulcers. M- dioica H mL/lOOg) also showed significant proieciioii against inaoi:"icii!Uci.u induced aruic ^lIcI,'i^. .!':J iifrthemiore, when admini<;tercd daily for 14 days accelerated the healing of chronic ulcers induced with acetic acid M. Jwranha did not show significant tlierapeuiic effects --v. ?hc latter t«'c models. It is concluded that the trait extracts of Mct. waniia and M. dioica show significant antiulcer effects but M dio-ra is more potent and therapeutically effective in ali die .ncdr^h tested. The precise mechanism of action reniains to be detennined.